# Find the Slope and Y-Intercept (6,-2) , (-8,-2) (6,-2) , (-8,-2)
Find the value of the slope.
Slope is equal to the change in y over the change in x, or rise over run.
m=change in ychange in x
The change in x is equal to the difference in x-coordinates (also called run), and the change in y is equal to the difference in y-coordinates (also called rise).
m=y2-y1x2-x1
Substitute in the values of x and y into the equation to find the slope.
m=-2-(-2)-8-(6)
Simplify.
Cancel the common factor of -2-(-2) and -8-(6).
Rewrite -8 as -1(8).
m=-2-(-2)-1⋅8-(6)
Factor -1 out of -1(8)-(6).
m=-2-(-2)-1(8+6)
Reorder terms.
m=-2-2⋅-1-1(8+6)
Factor 2 out of -2.
m=2(-1)-2⋅-1-1(8+6)
Factor 2 out of -2⋅-1.
m=2(-1)+2(1)-1(8+6)
Factor 2 out of 2(-1)+2(–1).
m=2(-1+1)-1(8+6)
Cancel the common factors.
Factor 2 out of -1(8+6).
m=2(-1+1)2(-1(4+3))
Cancel the common factor.
m=2(-1+1)2(-1(4+3))
Rewrite the expression.
m=-1+1-1(4+3)
m=-1+1-1(4+3)
m=-1+1-1(4+3)
Simplify the numerator.
Multiply -1 by -1.
m=-1+1-1(4+3)
m=0-1(4+3)
m=0-1(4+3)
Simplify the expression.
m=0-1⋅7
Multiply -1 by 7.
m=0-7
Divide 0 by -7.
m=0
m=0
m=0
m=0
Find the value of the y-intercept.
Substitute the value of m into the slope-intercept form of the equation, y=mx+b.
y=(0)⋅x+b
Substitute the value of x into the slope-intercept form of the equation, y=mx+b.
y=(0)⋅(6)+b
Substitute the value of y into the slope-intercept form of the equation, y=mx+b.
-2=(0)⋅(6)+b
Rewrite the equation as (0)⋅(6)+b=-2.
(0)⋅(6)+b=-2
Simplify (0)⋅(6)+b.
Multiply 0 by 6.
0+b=-2
b=-2
b=-2
b=-2
The values of the slope and y-intercept are m=0 and b=-2.
m=0
b=-2
Find the Slope and Y-Intercept (6,-2) , (-8,-2)     